A Social Constructivist Theory of Batad Leadership in Ifugao Philippines using the Grounded Theory Approach - Ilac, Emerald Jay D (Archīum Ateneo, 2018)
Using a social constructivist approach, I aimed to better understand the leadership process within an identified context of the indigenous Batad society of Banaue, Ifugao in the Philippines. This topic is particularly important as The National Commission on Indigenous Peoples of the Philippines indicates that roughly 15% of the Philippine population identifies as part of an indigenous group. Methods included conducting group and individual interviews with those in the Batad society, as well as gathering ethnographic observations and analyzing the qualitative process of social constructivist grounded theory. Results theorize a process model demonstrating interactions among leadership precursors, agency, and value. The present study exposes the importance of the concept of communality, which is the expectation that leaders are to act in preference for community welfare over and above family and self, a concept overlooked in most non-Filipino leadership studies.